Research Trends in Analytical Thinking Skills for Science Education: Insights, Pedagogical Approaches, and Future Directions - Bayani, Faizul; Rokhmat, Joni; Hakim, Aliefman; Sukarso, AA (Faculty of Engineering and Applied Science, 2025)
In the rapidly evolving 21st century, fostering analytical thinking skills has become a critical objective in science education, enabling students to solve complex problems and adapt to knowledge-driven economies. This systematic literature review, covering research from 2013 to 2024 and focusing on Scopus-indexed journals (Q1–Q3), aims to identify trends in analytical thinking research, explore effective pedagogical approaches, and analyze methodological diversity in the field. Using the PRISMA framework, 60 peer-reviewed studies were systematically selected and analyzed through both quantitative and qualitative methods, with thematic coding and tools like Vosviewer employed to uncover patterns and themes. The findings highlight a surge in research during 2020–2021, driven by the global shift to remote learning, and emphasize the effectiveness of innovative teaching strategies such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), and Inquiry-Based Learning (IBL) in fostering analytical skills. The review also underscores the role of technological interventions, such as virtual labs and simulations, in enhancing student engagement and cognitive development. However, gaps were identified, including the need for longitudinal studies and standardized evaluation metrics to assess long-term impacts. The study concludes that integrating evidence-based, scalable strategies across diverse educational contexts is essential for promoting analytical thinking as a core competency. Future research should prioritize interdisciplinary approaches and leverage emerging technologies to address these gaps. These findings provide actionable insights for educators, researchers, and policymakers aiming to advance science education and prepare students for the challenges of a dynamic world.